‫ﻗﺮار‬‫اﻟﺮﻓﻊ‬ ‫ﰲ‬ ‫رأس‬ ‫ﻣﺎل‬ ‫اﳌﺆﺳﺴﺎت‬ ‫اﻻﻗﺘﺼﺎدﻳﺔ‬ ‫ﺑﲔ‬ ‫ﳏﺪودﻳﺔ‬ ‫أداء‬ ‫اﻟﺒﻮرﺻﺔ‬ ‫واﻟﻨﻈﺎم ‬‫اﳌﺼﺮﰲ‬ ‫دراﺳﺔ‬ ‫ﺣﺎﻟﺔ‬ ‫ﻣﺆﺳﺴﺎت‬ ‫ﻣﺪرﺟﺔ‬ ‫ﰲ‬ ‫ﺑﻮرﺻﺔ‬ ‫اﳉﺰاﺋﺮ‬ ‫–‬‫أﻟﻴﺎﻧﺲ‪،‬ﺑﻴﻮﻓﺎرم‬ ‫‪-‬‬ - ‫ﺳﻬﺎم ‬‫ﻃﺒﻴﺐ‬; ‬‫ﺛﻠﻴﺠﺔ‫ ﺷﻔﺮور ‬ (My University, 2019)
The subject of the decision to raise the capital of economic institutions has attracted the attention of many researchers in the field of financial management, because the institution seeks to rationalize its financial decisions in order to build a capital structure that helps to grow and develop. The aim of this study is to look for the effect of the decision to raise the capital of the institution In light of the activity of the stock market and the banking market. In order to achieve this objective, the analytical descriptive method was used to determine the status of the capital structure. The hypotheses were also selected using the event method to evaluate the decision of Alianas and Biofarm. This study reached a number of results, the most important of which was that the decision to raise the capital of the Algerian institution is subject to a range of variables resulting from the financial situation of both the stock market and the banking system.